2022
DOI: 10.1161/jaha.122.025663
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Quantitative Flow Ratio Virtual Stenting for Guidance of Serial Coronary Lesions Intervention

Abstract: Background Coronary physiology measurement in serial coronary lesions with multiple stenoses is challenging. Therefore, we evaluated the feasibility of Murray fractal law‐based quantitative flow ratio (μQFR) virtual stenting for guidance of serial coronary lesions intervention. Methods and Results Patients who underwent elective coronary angiography and had 2 serial de novo coronary lesions of 30% to 90% diameter stenosis by visual estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Previous landmark studies have demonstrated the instrumental value of the QFR in guiding the PCI procedure and further improving the clinical prognosis ( 10 12 ). The residual QFR is a predicted QFR value based on coronary angiographic imaging that simulates successful stent implantation in the culprit lesion, correlates well with the post-PCI FFR and QFR, and predicts the occurrence of adverse events after revascularization ( 13 , 14 , 16 , 22 ). A retrospective analysis of the PANDA III trial showed that the predicted clinical outcome of residual QFR-guided PCI was superior to that of angio-guided PCI ( 15 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous landmark studies have demonstrated the instrumental value of the QFR in guiding the PCI procedure and further improving the clinical prognosis ( 10 12 ). The residual QFR is a predicted QFR value based on coronary angiographic imaging that simulates successful stent implantation in the culprit lesion, correlates well with the post-PCI FFR and QFR, and predicts the occurrence of adverse events after revascularization ( 13 , 14 , 16 , 22 ). A retrospective analysis of the PANDA III trial showed that the predicted clinical outcome of residual QFR-guided PCI was superior to that of angio-guided PCI ( 15 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the residual QFR, a cardiologist can identify the major lesion from a functional perspective, further optimizing the PCI strategy. The residual QFR-guided PCI strategy was superior to angiographic guidance in reducing the 2-year incidence of target vessel failure (TVF) ( 15 , 16 ). However, research into the predictive value of the residual QFR for adverse events is limited, particularly in patients whose residual QFR does not match their post-PCI QFR.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the study by Guan and colleagues 14 is informative and sheds light for further research. Once streamlined, QFR may serve as a useful tool to supplement coronary angiography, but further studies are needed to establish its role in predicting residual FFR following PCI to help procedural planning as well as broadening the role of noninvasive tools to assess microvascular function.…”
mentioning
confidence: 84%
“…In this issue of the Journal of the American Heart Association ( JAHA ), Guan and colleagues 14 report the results of a prospective study assessing the utility of uQFR to virtually plan PCI. Participants presented with 2 serial lesions that were visually estimated between 30% and 90% in the same epicardial vessel and separated by at least 10 mm of an angiographically‐looking normal segment.…”
mentioning
confidence: 99%
See 1 more Smart Citation